Tuning of high-temperature dielectric properties in the system (Bi0.5Na0.5)TiO3–BaTiO3–CaZrO3. Issue 15 (1st August 2022) - Schulz, Thomas; Knauer, Andrea; Schaaf, Peter; Töpfer, Jörg
Abstract: Solid solutions of the (1-x)(0.94Bi0.5 Na0.5 TiO3 -0.06BaTiO3 )-xCaZrO3 system are regarded as promising dielectrics for high-temperature capacitors as they exhibit a remarkable flat trend of the permittivity over a large temperature range coupled with comparable low dielectric losses. In this work, the composition 0.8(0.94Bi0.5 Na0.5 TiO3 -0.06BaTiO3 )-0.2CaZrO3 was chosen in an attempt to optimize especially the high-temperature dielectric properties above 200 °C. In particular, the influence of excess bismuth to account for element losses caused by evaporation, and the effect of manganese as acceptor dopant are reported. Conventional solid-state reaction route was used to synthesize selected compositions. X-ray diffraction was used to confirm a pseudo-cubic perovskite main phase in all examined compositions, although small traces of a zirconia secondary phase were also detected. All samples exhibit an expected flat trend of the relative permittivity with a maximum deviation of the permittivity lower than 15% between −80 °C and 300 °C. The unmodified base composition shows small dielectric loss (<2%) between −55 °C and 265 °C. By using small quantities of manganese doping, the small-loss temperature range was extended (−70 °C and 300 °C). Excess bismuth also affects the temperature-dependent dielectric losses, resulting in a narrowed temperature range, eventually limiting the application possibilities.